A system for shotgun DNA sequencing. - Messing, J (1981)
A multipurpose cloning site has been introduced into the gene for beta-galactosidase (beta-D-galactosidegalactohydrolase, EC 3.21.23) on the single-stranded DNA phage M13mp2 (Gronenborn, B. and Messing, J., (1978) Nature 272, 375-377) with the use of synthetic DNA. The site contributes 14 additional codons and does not affect the ability of the lac gene product to undergo intracistronic complementation. Two restriction endonuclease cleavage sites in the viral gene II were removed by single base-pair mutations. Using the new phage M13mp7, DNA fragments generated by cleavage with a variety of different restriction endonucleases can be cloned directly. The nucleotide sequences of the cloned DNAs can be determined rapidly by DNA synthesis using chain terminators and a synthetic oligonucleotide primer complementary to 15 bases preceeding the new array of restriction sites.